Agent-based simulation of trust networks and opportunistic behaviours of hydraulic infrastructure project participants - Jiaqi Lv; Xiang Wang; Yaoyao Chen (PLoS ONE, 2025)
Opportunistic behaviour has become a research hotspot in hydraulic infrastructure project management owing to its serious damage to the cooperation efficiency of all participants in a project. The trust networks formed by each participant can restrain opportunistic behaviour, but due to the dynamic evolution of the networks, its research should adopt a dynamic paradigm. The structure and evolution of trust networks can be simulated using computer simulations and modelling. This study explores the influence mechanism of the structural characteristics of trust networks on the diffusion of opportunistic behaviour. The results show that trust network density has a positive effect on inhibiting the implementation tendency of opportunistic behaviour. However, the centralisation of trust networks has a negative correlation with the degree of inhibition of opportunistic behaviour.